Advancements in cotton defoliation: From chemical harvest aids to genomic innovations - Selvamani, Sanyasi; Ravikesavan, Rajasekaran; Manikanda Boopathi, Narayanan; Sakthivel, Nalliappan; Kannan, Nallathambi; Karthik, Palanisamy; Kumaresan, Dharmalingam (Plant Science Today, 2025)
Cotton is a crucial crop in the global textile market and its increasing demand necessitated the adoption of improved agronomic practices. Defoliation plays a vital role in enhancing harvesting efficiency and indirectly improves fibre quality by minimizing leaf trash contamination during mechanical harvest. This review critically examines the physiological, hormonal and molecular mechanisms governing defoliation in cotton, with particular focus on the roles of auxin, ethylene, abscisic acid and jasmonic acid in regulating leaf abscission. The complex interactions between these hormones influence the activation of the abscission zone and the efficiency of leaf drop. However, several challenges affect the performance of defoliants, including environmental variability, genetic differences among cultivars and the potential health and ecological risks associated with chemical defoliants. The differential response of cotton cultivars to defoliants complicates application strategies, often leading to inconsistent defoliation and increased production cost. To address these challenges, a multi-faceted approaches like deeper understanding of the molecular basis of defoliation, enhancement of defoliant efficacy and the development of cultivars with enhanced defoliant response are essential. This approach is supported by precision agriculture technologies, such as Unmanned Aerial Vehicle (UAV)-assisted spraying, optimized harvest-aid timing and dosage and strategic defoliant selection. Additionally, the identification of candidate genes and QTLs associated with defoliation response opens new opportunities for developing cultivars optimized for mechanical harvesting. This review stresses the need for integrated strategies that harmonize increased cotton production with ecological considerations. It calls for future research on sustainable practices, improved defoliation methods and the development of genotypes responsive to defoliants to enhance resilience in cotton cultivation.